Acalypha subgenus Linostachys (Euphorbiaceae, Acalyphoideae): a global review - Muñoz-Rodríguez, Pablo; Cardiel, José María; Atha, Daniel (Phytotaxa, 2014)
A critical review of Acalypha subgenus Linostachys (Euphorbiaceae: Acalyphoideae) worldwide is presented. As a result 28 species, 6 of which were not previously recognized within the subgenus, are accepted and 5 new synonyms are proposed. Comprehensive nomenclatural information is supplied and 16 lectotypes and one neotype are designated. An identification key and geographic information, including a distribution map of the subgenus, are also provided. This is the first treatment of subgenus Linostachys since Pax and Hoffmann’s monograph in 1924.